(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
Objective: To adapt The SACSTM Instrument: assessing and classifying peristomal skin lesion to the Brazilian Portuguese language and to evaluate the Content Validity Index (CVI) and the interobserver reliability. Method: Methodological study with a quantitative approach. Two translators developed the cross-cultural adaptation for translation and two others for back-translation. The interobserver agreement was achieved by the analysis of 41 photographs by two enterostomal therapist nurses. Results: SACSTM obtained CVI = 1. The agreement for classification of lesions was 41.18% and K = 0.2444, for the topographic location was 46.67% and K = 0.3151, resulting in considerable and extremely significant agreement, with p < 0.001. Conclusion: The study certified the version adapted to the Brazilian Portuguese language and attested that it requires the qualification of enterostomal therapists and generalist nurses in clinical practice.